Oral mucoadhesive patch of green betle leaf, areca nut, and gambier can reduce the size of traumatic ulcer lesion - Suparno, Nilasary Rochmanita; Rizqinavia, Ghina AP; Putri, Nanda Anggita Permata (Odonto : Dental Journal, 2023)
Background: Although topical corticosteroids and antibiotics are frequently prescribed to treat traumatic ulcers, both medications have disadvantages. In addition, topical application of the drug is ineffective because it can be washed off by saliva. In order to speed up the healing of traumatic ulcers, it is believed that the oral mucoadhesive patches will adhere to the ulcer for a longer amount of time. Methods: This study was a pure laboratory experiment with a post-test only randomized control group design. The study samples were 32 white rats (Rattus norvegicus) of the Wistar strain with traumatic ulcers on the buccal mucosa. The sample was divided into 2 groups: (1) the control group, which was only given analgesics (5% EMLA); and (2) the treatment group, which was given analgesics (5% EMLA) and oral mucoadhesive patches (a combination of ethanol extracts of green betel leaf, areca nut, and gambier). Each group received treatment twice a day for 10 days. Then the diameter of the traumatic ulcer lesion was measured with a digital caliper on days 1–10 from the yellowish-white part. The data obtained were analyzed using an independent t-test. Results: There was a significant difference in the diameter reduction of traumatic ulcer lesions between the control group and the treatment group (p